Posttraumatic Pseudoarthrosis of a Clavicle Fracture in an 11-Year-Old Girl: A Case Report and Analysis - Marco Odorizzi; Maurice FitzGerald; Jorge Gonzalez; Dario Giunchi; Flurim Hamitaga; Vincenzo De Rosa (Case Reports in Orthopedics)
Clavicular fractures are some of the most common bone injuries in the paediatric population, yet the rates of nonunion are very low under 18 years. To the best of our knowledge, posttraumatic nonunion of the clavicle in a paediatric population is rarely reported. We report the case of an 11-year-old girl who presented with a nondislocated fracture of the midshaft to the proximal third of the right clavicle. Initial conservative treatment by sling immobilization demonstrated radiologically confirmed healing at 3 months. However, at 1-year follow-up, she presented with painful nonunion. Diagnostic MRI and CT exams confirmed a pseudoarthrosis, requiring elective open reduction and internal fixation with the aid of an ipsilateral iliac crest bone graft.